2022
DOI: 10.3389/fgene.2022.921051
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Nanoparticles With pH-Sensitive Co-Delivery of Temozolomide and siEGFR to Ameliorate Glioma Therapy

Abstract: Glioblastoma (GBM) is one of the most lethal forms of human cancer, with very few long-term survivors. In addition to surgery, chemotherapy is still an important strategy. Unfortunately, GBM chemotherapy faces two main challenges: first, in GBM, epidermal growth factor receptor (EGFR) overexpression results in chemoresistance; second, temozolomide (TMZ) lacks target specificity, which can lead to a reduction in the concentration and side effects in GBM. Nowadays, with the development of nanomedicine systems fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…They demonstrated that in rats bearing an orthotopic glioma model, micelles containing both strategies reduced the tumors from ~ 200 mm 3 and ~ 170 mm 3 in the case of the administration of siRNA and TMZ, respectively, to ~ 75 mm 3 with both therapies 79 . Moreover, in a recent study, Wang et al co-delivered TMZ with an EGFR-siRNA in polymeric nanoparticles and observed that while in mice treated with TMZ, tumors grew rapidly with a glioma inhibition rate of 164.3, the tumor inhibition rate for animals treated with both drugs was 15.3, suggesting a high antitumor efficacy and synergic effect 77 .…”
Section: Improving Tmz Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that in rats bearing an orthotopic glioma model, micelles containing both strategies reduced the tumors from ~ 200 mm 3 and ~ 170 mm 3 in the case of the administration of siRNA and TMZ, respectively, to ~ 75 mm 3 with both therapies 79 . Moreover, in a recent study, Wang et al co-delivered TMZ with an EGFR-siRNA in polymeric nanoparticles and observed that while in mice treated with TMZ, tumors grew rapidly with a glioma inhibition rate of 164.3, the tumor inhibition rate for animals treated with both drugs was 15.3, suggesting a high antitumor efficacy and synergic effect 77 .…”
Section: Improving Tmz Limitationsmentioning
confidence: 99%
“…In fact, nanosystems are being developed to be encapsulated together with TMZ. These agents include other chemotherapeutic agents (paclitaxel [74], doxorubicin [37], and 5-Fluoracil [39]); inhibitors [75,76]; nucleic acids [58,[77][78][79][80]; photosensitizers for photodynamic therapy [81,82]; other nanomaterials for photothermal therapy [83,84] and magnetic hyperthermia [85][86][87] and other molecules [59,62,88] (summarized in Table 2 and Figure 3). In vitro [82] Curcumin…”
Section: Improving Tmz Resistance: Combined Therapymentioning
confidence: 99%
“…Through the silencing of the proliferating EGFR gene and the enhanced concentration of TMZ, a robust apoptotic response was triggered, resulting in a significant inhibition of tumor growth. 137 The implementation of multimodal therapeutic combinations, encompassing the integration of diverse therapeutic approaches or therapeutic agents with distinct molecular mechanisms that target glioma and other solid tumors, resulting in enhanced cytotoxic effects, plays a pivotal role in advancing patient outcomes and represents an efficacious treatment strategy. Nowadays, pyroptosis has notably been gained extensive attention from clinicians and researchers.…”
Section: Nanosystems For Glioma Treatmentmentioning
confidence: 99%
“…This nanovesicle successfully encapsulated both the chemotherapeutic drug TMZ and the epidermal growth factor receptor (EGFR) inhibitor EGFR‐siRNA within nano‐carriers, facilitating their efficient delivery into U87 cells. Through the silencing of the proliferating EGFR gene and the enhanced concentration of TMZ, a robust apoptotic response was triggered, resulting in a significant inhibition of tumor growth 137 …”
Section: Current Management Of Gliomasmentioning
confidence: 99%